Imiona chrzestne mieszkańców Iskrzyni w XIX wieku na podstawie metryk parafi i Krościenko Wyżne z lat 1848-1900 - Rachwał, Piotr (Archiwa, Biblioteki i Muzea Kościelne, 2010)
The basic sources for research on the names of Iskrzynia inhabitants in the 19th century were baptismal registers from the years 1848-1900. The author focused on different factors which could affect the choice of a Christian name, that is to say, family tradition, literary influence, changing fashion. It was also pointed out that the relation between the date of baptism and a saint patron played an important role in deciding on a name for a child. Over 47% of boys received the names of patrons whose days were in the month of their baptism, for girls the percentage was almost 26%. The range of Iskrzynia inhabitants’ names given in baptism is wide. In the studied period there were 59 kinds of male names and 59 female ones. The most popular male names were: Jan, Stanisław, Franciszek, Józef and female ones: Marianna, Aniela, Katarzyna and Helena.